2019
DOI: 10.15280/jlm.2019.9.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Interventional Program about Mothers' Behavior Related to Exclusive Breast Feeding: Findings of Planned Behavior Theory-Based Research

Abstract: BackgroundPromotion of exclusive breast feeding is known as a savior strategy, to reduce infantile mortality. The theory of planned behavior is an appropriate theory to explain the effect of psychosocial factors on infant feeding behavior. This study aimed to evaluate impact of planned behavior theory-based education on the behavior of pregnant women related to exclusive breast feeding in Arak city, 2016–17.MethodsThis study is an interventional study that was done on 101 pregnant women with gestational age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
3
3
0
Order By: Relevance
“…Also, the behavioral intention was enhanced by watching educational videos and reading the booklets. This finding was consistent with some studies; for example, Ghaffari et al on increasing mothers' intention for the behavior of pregnant women related to exclusive breastfeeding (36).…”
Section: Discussionsupporting
confidence: 93%
“…Also, the behavioral intention was enhanced by watching educational videos and reading the booklets. This finding was consistent with some studies; for example, Ghaffari et al on increasing mothers' intention for the behavior of pregnant women related to exclusive breastfeeding (36).…”
Section: Discussionsupporting
confidence: 93%
“…Also, behavioral intention was enhanced by watching educational videos and reading the booklets. This nding was consistent with the some studies like the one by Ghaffari et al on increasing mothers' intention for behavior of pregnant women related to exclusive breast feeding [37].…”
Section: Discussionsupporting
confidence: 93%
“…This study's objective was to determine knowledge and skills retention of breastfeeding after completion of an educational class. Consistent with previous findings that breastfeeding education enhances women's knowledge and skills to breastfeed, 19,20 all participants in our study reported increased knowledge of bringing baby to the breast. Thus, women's confidence to breastfeed their infant is enhanced through knowledge obtained from breastfeeding education.…”
Section: Discussionsupporting
confidence: 92%